Divided armies : inequality and battlefield performance in modern war - Lyall, Jason (Princeton studies in international history and politics., 2020)
"How do armies fight and what makes them victorious on the modern battlefield? In Divided Armies, Jason Lyall challenges long-standing answers to this classic question by linking the fate of armies to their levels of inequality. Introducing the concept of military inequality, Lyall demonstrates how a state's prewar choices about the citizenship status of ethnic groups within its population determine subsequent battlefield performance. Treating certain ethnic groups as second-class citizens, either by subjecting them to state-sanctioned discrimination or, worse, violence, undermines interethnic trust, fuels grievances, and leads victimized soldiers to subvert military authorities once war begins. The higher an army's inequality, Lyall finds, the greater its rates of desertion, side-switching, casualties, and use of coercion to force these soldiers to fight. In a sweeping historical investigation, Lyall draws on Project Mars, a new dataset of 250 conventional wars fought since 1800, to test this argument. Project Mars breaks with prior efforts by including overlooked non-Western wars while cataloguing new patterns of inequality and wartime conduct across hundreds of belligerents. Combining historical comparisons and statistical analysis, Lyall also marshals evidence from nine wars, ranging from the Eastern Fronts of World War I and II to less familiar wars in Africa and Central Asia, to illustrate inequality's effects. Sounding the alarm on the dangers of inequality, Divided Armies offers important lessons about battlefield performance over two centuries--and for wars still to come"--